Exploring the prospective role of relationships and psychological distress in postpartum risk of intergenerational continuity of child maltreatment - Langevin, Rachel; Hébert, Martine; Bernier, Annie; Frappier, Jean-Yves (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: This prospective longitudinal study aimed to explore the role of family relationships (romantic satisfaction and mother-infant bonding) and psychological distress in the associations between four child maltreatment (CM) subtypes (sexual, physical, and emotional abuse, neglect) and early child abuse potential in young mothers.